Traditional Administrative System and Modern-Day Governance in Nigeria: A Comparative Analysis - Sulaiman, Yushau Abubakar; Ibrahim, Ajao Yusuf (Journal of Governance, 2024)
Assertions that say there were no organized political administrative systems in the pre-colonial traditional societies of Africa should be utterly discarded. This is because there were established formal laws of engagement in the pre-independence Nigerian societies. However, the coming of colonialists brought a pose to these traditional systems of administration, with its antecedent consequences as problems of corruption, elite rulers, insecurity, economic meltdown, decline in moral manners, power tussle, and ethnic jingoism, among others. Because the traditional administrative system in Nigeria prior to the coming of colonial masters was free of this menace to some extent, it was the present system that was fashioned or modelled by the white men that brought in these problems. This paper examined the tenets of the three major traditional societies in Nigeria in comparison with the current governance system in order to deduce. It was discovered that all the problems showcasing in present Nigeria are due to the eroding and non-inclusion of traditional rulers roles into the modern-day government practically and  constitutionally. The paper sourced its materials through secondary sources. It was recommended that the pre-independence features of these traditional societies should be inculcated, and they should also be given constitutional rights because they are the custodians of their societies and are by law divine in nature.